Ethical aspects of cadaveric transplantation: Focus on the nursing profession - Živanović Dejan; Doronjski Aleksandra (Association of Nurses Technicians and Midwives, 2017)
For the last fifty years, transplantation of tissue and organs has enabled the continuation of life for many people who, due to the nature of the disease, would have been sentenced to death earlier. It also raised many moral dilemmas that led to the social need for precise legal and ethical regulation of this field of medical activity, especially when are concerned with cadaveric donors. Nurses play an active role in caring different categories of patients, including potential donors of tissues and organs, and promotion of donors, the way in which they participate in the transplant team, participation in the process of obtaining transplant organs, and how to implement nursing care for potential donors of tissues and organs, represent the most often professional activities of nurses in which ethical dilemmas occur.